Hibriditas Kolonial Dan Nilai Pendidikan Karakter Pada Novelet Dorodasih Karya Imam Budhi Santosa - Riska Dewi Widyaningrum (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2017)
AbstractThis study aims to (1) describe and explain the colonial hybridity Dorodasih novella by Imam Budhi Santosa, and (2) to describe the value of character education at Dorodasih novella by Imam Budhi Santosa. This study used a qualitative descriptive method to describe the hybridity and the educational value of the character in the novella Dorodasih of Imam Budhi Santosa. The data in this study of words, phrases, sentences contained in Dorodasih novella by Imam Budhi Santosa, published by Reader Literature LKIS Yogyakarta. Data collection techniques used in this study is a non-interactive technique. Mechanical noninteractive done by intensive reading of the novella and make record actively with content analysis. The validity of the data used to use data triangulation to collect the same data. In a sense the same or similar data will be valid truth when used several different data sources. The conclusions from the results of this study as follows: (1) the existence of the colonial hybridity Dorodasih novella by Imam Budhi Santosa, and (2) the value of character education that existed at novelet Dorodasih is hard work.—AbstractThis study aims to (1) describe and explain the colonial hybridity Dorodasih novella by Imam Budhi Santosa, and (2) to describe the value of character education at Dorodasih novella by Imam Budhi Santosa. This study used a qualitative descriptive method to describe the hybridity and the educational value of the character in the novella Dorodasih of Imam Budhi Santosa. The data in this study of words, phrases, sentences contained in Dorodasih novella by Imam Budhi Santosa, published by Reader Literature LKIS Yogyakarta. Data collection techniques used in this study is a non-interactive technique. Mechanical noninteractive done by intensive reading of the novella and make record actively with content analysis. The validity of the data used to use data triangulation to collect the same data. In a sense the same or similar data will be valid truth when used several different data sources. The conclusions from the results of this study as follows: (1) the existence of the colonial hybridity Dorodasih novella by Imam Budhi Santosa, and (2) the value of character education that existed at novelet Dorodasih is hard work. DOI: 10.15408/al-turas.v23i1.4802